TRAUMATIS SEBAGAI EKSPRESI DALAM BUSANA WANITA ANTI-FASHION - Fegelia Rahmadani; Arfiati Nurul Komariah (Universitas Mercu Buana, 2021)
The fraumatic issue upon childern need to be expose to public as one of social issue to notice in the society. In this writing, case is being responed as an expression of the craftmanship of women’s fashion. This expression roled as the representation of mother. The final products of this thesis is a critic work was a critic about behasioral digression to the attitude of mothers in rising their children that caused a traumatic effect on the children itself. Fashion, in this cuse, used as communication media to communicat experientes and traumatic phenomenon throgh partice, artefac, intuition, and metaphor to express the emotional values that comes from social enviarnment.The method used in this work is a practice based on research method, Process that used logical understanding or reason in creating research into art creation can produce academic document that has function to help communicate the description of the work, both conceptually and contextually. Meanwhile, the theory used in this work was the theory of art function and imagination. The works itself is manifested using a manipulating of fabric technique which will produce a response to the traumatic feeling of the children.The writings of this final assignment are in the form of eight design works, and five of that will come to a work realization. Each work represent the perspective values of the author about traumatic phenomenon of the children as the manifestation of behavior digression of mothers in rising or educating their children. In addition, the design of women’s clothing was an anti-fashion style inspired by Japanese design Rei Kawakubo. Anti-fashion was a form of fashion innovation that do not have timeline of fashion and break the gap of fashion because it does not fond of the market trends and desires.